Efficacy of subcutaneous bortezomib in the management of patients with multiple myeloma or relapsed mantle cell lymphoma - Podar, Klaus (Clinical medicine insights. Therapeutics, 2014)
The identification of the ubiquitin-proteasome system as a new therapeutic target has been one of the most recent successes in cancer treatment. The development and clinical approval of the first-in-class proteasome inhibitor, bortezomib has revolutionized the treatment of multiple myeloma (MM) and mantle cell lymphoma (MCL). In MM, bortezomib is now integrated in induction, conditioning, consolidation, maintenance, and salvage treatment protocols. Bortezomib-based regimens provide high remission rates and confer significant survival advantage compared to conventional chemotherapy in both the bone marrow transplant and non-transplant setting. In MCL, overall response rates in patients who have received at least one prior therapy range from 30 to 45%, even in chemotherapy resistant patients. Clinical trials to further improve the sequencing of bortezomib-containing combination therapies are ongoing. Until recently, intravenous injection was the standard route of bortezomib administration. However, severe adverse side effects, peripheral neuropathy in particular, were observed in up to 16% of MM patients and up to 54% of MCL patients treated with intravenous bortezomib, with grade 3 and 4 in 11 and 12% of patients, respectively. Moreover, complete remission rates, if at all, are low and duration of response is short both in MM and MCL. These limitations may be overcome by changing the method of bortezomib administration as well as by rationally combining bortezomib with other therapeutic agents. Indeed, recent data demonstrate that subcutaneous bortezomib administration is non-inferior to intravenous administration, with an improved systemic safety profile, good local tolerance, and a more convenient route of administration. Based on these data, subcutaneous bortezomib injection was approved as a supplemental new drug application for all approved indications in MM and MCL after at least one prior therapy. More than 30 clinical trials in MM and MCL are currently ongoing to evaluate the efficacy and safety profile of subcutaneous bortezomib also in induction, maintenance, and salvage therapy.